Subject- and joint-specific strategies used by male basketball players to maximize countermovement jump height - Kipp, K.; Kiely, M.; Giordanelli, M.; Malloy, P.; Geiser, C. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this project was to study the subject- and joint-specific strategies that male basketball players use to increase countermovement jump (CMJ) height. Lower extremity joint kinematics and kinetics were recorded as 11 male, NCAA Division I basketball players performed 8-10 CMJ with increasing effort. Correlations between maximal potential energy of players` centre-of-mass (surrogate for CMJ height) and the amount of eccentric and concentric work done at the hip, knee, and ankle joint Singlesubject and group-average analyses were used to study. The group-average analysis showed that all joint work variables predicted potential energy, whereas the singlesubject analysis revealed varying levels of subject-specific correlations (i.e., joint-specific CMJ strategies) that did not necessarily reflect the group-average data.